Studies Of Clitoria Ternatea Linn. Root Extract On Behavioural Effects And In Vivo Hippocampal Synaptic Plasticity In A Rat Model Of Chronic Cerebral Hypoperfusion - Damodaran, Thenmoly K (2018)
Clitoria ternatea Linn. (CT) is a native plant in tropical countries like Malaysia. The root part of the plant has been studied extensively for its pharmacological activities. However, its contribution towards learning and memory enhancement together with in vivo synaptic plasticity in a chronic cerebral hypoperfusion (CCH) rat model has yet to be explored. For quality control purposes, taraxerol content (0.15% ± 0.01) in the methanolic extract of CT root was determined using validated gas chromatography-mass spectrometry (GC-MS) analytical method. In the present study, the permanent bilateral occlusion of common carotid arteries (PBOCCA) surgery method was employed to develop CCH model in rats. The acute and chronic (28 days) treatment of CT root extract at doses of 200 and 300 mg/kg, p.o. resulted in a significant enhancement in memory retention of the passive avoidance task. Effects of CT root extract were further assessed in the Morris water maze task. The results demonstrate that CT root extract (200 and 300 mg/kg, p.o.) treatment restored spatial learning and reference memory impairments induced by CCH. Chronic treatment of CT root extract (200 and 300 mg/kg, p.o.) was also found to diminish CCH-induced neuronal damage in the CA1 region of the hippocampus. An increased acetylcholinesterase (AChE) activity in the frontal cortex and hippocampus of the PBOCCA rats was significantly inhibited by the CT root extract at a high dose (300 mg/kg, p.o.). In synaptic plasticity study, CT root extract (200 and 300 mg/kg, p.o.) restored the CCH-induced in vivo hippocampal long-term potentiation (LTP) suppression at the Schaffer collateral CA3-CA1 synapse. These results indicate that CT root extract may affect learning and memory functions in PBOCCA rats via LTP facilitation. CT root extract (300 mg/kg, p.o.) did not show any improvement on spatial memory and hippocampal LTP in scopolamine (muscarinic receptor antagonist; 1.0 mg/kg, i.p.) pre-treated PBOCCA rats. In toxicity study, repeated doses of CT root extract (100, 200 and 300 mg/kg, p.o.) were found to be safe in PBOCCA rats after 28 days treatment. In conclusion, the methanolic extract of CT root extract restored the learning and memory deficits and in vivo synaptic plasticity impairment in a CCH rat model, thus supporting the therapeutic potential of CT root extract in the treatment of vascular dementia (VaD).